Sedation of Adults with Orally Administered Midazolam in Dentistry - A Retrospective Study - Marika Storskrubb; Pia Gabre (Medical Journals Sweden, 2024)
Objective: The use of midazolam (MZ) has increased in dentistry, but the effect in adults is sparsely studied. The aim of this study was to investigate doses, effects, and side effects of orally administered MZ as a sedative for adults in a dental care organization. Material and methods: A retrospective record review was performed including all adult patients in the dental care organization ≥20 years receiving MZ, identified through a logbook for addictive drugs, during 2020. From patients' records, the following data were extracted: age, gender, medical history, reason for sedation, performed treatments, doses, effects, and side effects of MZ.  Results: In total, 265 patients on 418 occasions had been sedated, which constituted 2.3 sedations per 1,000 visits and 3.3 sedations per 1,000 treated patients. Mean age was 40.8 years and 67.7% were females. The most common reason for sedation was anxiety. Mean dose in primary dental clinics was 7.9 mg and in specialist clinics, 6.8 mg (p < 0.001). Older patients (>70 years) had lower doses than younger (p < 0.001), while no difference was found between ages 55-70 years and those who were younger. Dental treatment was completed in 91.9% of occasions, and side effects were registered in 2.2%. Successful dental treatment was related to type of treatment performed. Conclusions: Sedation is rarely used, particularly in primary dental care, and the use varies widely between clinics. MZ administered by dentists seems to be safe and effective. A sedation record should be used to make patient data such as weight and medical conditions available.